Human papillomavirus infection rate, distribution characteristics, and risk of age in pre- and postmenopausal women - Yan Shen; Jing Xia; Huihui Li; Yang Xu; Sanping Xu (BMC, 2021)
Abstract Background The incidence rate of cervical cancer is increasing yearly. The persistent infection of high-risk human papillomavirus (HPV) is the main factor leading to cervical cancer. HPV infection is double peak type. This study aimed at analyzing the HPV distribution characteristics, infection rate, and risk of age in pre- and postmenopausal women. So as to provide reference for the prevention of HPV infection and cervical cancer screening strategy. Methods A retrospective analysis of 4614 women who underwent cervical cytology, and HPV examination from January 2018 to October 2019 at the healthcare department of Wuhan Union Hospital was done. We explored the characteristics and distribution of HPV infections around the menopause, then comparing the infection rate of HPV in postmenopause and over 65 years old, in order to analyze the influence of different ages on HPV infection. Results Generally, the HPV infection rate was 13.10% (539/4115), whereby the high-risk subtype constituted 73.84% (398/539) of all positive cases. On the other hand, the HPV39 infection was more common in postmenopausal women; however, there was no significant difference in the distribution of the other types in the pre- and postmenopausal women. The first four types were 52/53/58/16. The results further showed that the rates of HPV infection before and after menopause were 12.34% (367/2975) and 15.09% (172/1140), respectively, which had no significant difference (P = 0.056), but more susceptible to high-risk HPV infection after the age of 65 (P = 0.041). Except for 40 years old to menopause, the infection rate of high-risk HPV in this age group was different from that in postmenopause (P = 0.023, 0.729 (0.555, 0.957)), other age groups had no significant effect on high-risk HPV infection. Conclusions It was concluded that whether menopause has nothing to do with HPV infection. Moreover, the risk of high-risk HPV infection in women aged 40 to premenopausal is relatively low, but the infection rate increases after 65. Hence the cutoff screening age should be appropriately prolonged.